Growth model Epping : a method of measurement and analysis of industrial growth - Horrell, Roy (School of Architecture, Planning and Geomatics, 2020)
This study, which commenced in 1971, is of a comparatively modern industrial township notionally conceived some 25 years ago on ground which, during the War Years, had been 'beneficially occupied' and, in other respects, laid to waste as an Artillary Range. The Range had other strategic advantages in that its necessarily extended shape and position over the epicentres of the minor eruptions that had occurred are of considerable centrallity for industriallists and the labour pools on which they would draw. Pinelands Garden City is on the West boundary and Langa Location on the South boundary of that portion of the Range which became known as Epping Industria No. 1. The predominantly Coloured Areas of Matroosfontein and Elsie's Rivier lay immediately to the East and North-East respectively and the other old established Coloured Area of Athlone, which has since grown enormously, was not far distant to the South. Goodwood, Parow and Bellville lie to the North and North-East. Cape Town City Centre lies approximately 10 kilometres to the West - See Location Plan No. 1.